Nutrient absorption curves in three lily (Lilium sp.) varieties and optimization of a fertilization program in a commercial farm in Heredia, Costa Rica - Barrantes-Infante, Bianca L. (2024)
The fertilizer program was evaluated and optimized in a lily commercial farm, after the development of nutrient absorption curves in the varieties Brunello, Algarve and Alma Ata. The lily plants were separated into organs to evaluate the fresh and dry at 80oC weights, every 15 days, in 3 plants per variety. Dry tissues underwent concentration analysis to obtain the nutrient absorption. Based on nutrient absorption curves 5 fertilization treatments were designed: a treatment that consisted in the fertilization program of the commercial farm;the requirement treatment; which included onlywhat the plant absorbs; an adjusted treatment, a treatment with out any granular application; and the control. These treatments were appliedto the Siberia variety during the growing cycle.The absorption curves showed that most of the nutrients are provided by the bulb during the first 4 weeks of a total cycle of 12 to 14 weeks. The contents of N, P and K in the bulbs at the moment of planting ranged from 144-178, 19-28 and 160- 174 mg.bulb-1, respectively, while for a production of 66 (Alma Ata) and 72 (Brunello and Algarve) shoots.m-2 the aerial part of the plant consumed 15-18, 1.2-1.6 and 26.7-40.3 g.m-2, respectively. In all varieties, the highest absorption of N, P and K occurred at the end of the life cycle. Therequirement treatment did not show significantdifferences from the treatment of the commercial farm, presenting the same level of production and quality; also, it produced the highest number of medium and large size plant with a commercial value. The requirement and adjusted treatments showed the highest number of large buttons (>5 cm). Foliar applications of fertilizers proved to be important, mainly because the treatment without any granular fertilizer application hadthe highest percentage (56%) of bulbs andadventitious roots with the best appearance.